Do physical activity intensity and sedentary behaviour relate to burnout among medical students? Insight from two Canadian medical schools - Morgan, Tamara; McFadden, Taylor; Fortier, Michelle; Sweet, Shane; Tomasone, Jennifer (Canadian Medical Education Journal, 2024)
Background: Medical school involves high expectations of medical students, which may increase their risk for burnout. Physical activity (PA) and sedentary behaviour (SB) are modifiable risk factors for burnout. However, medical students are insufficiently taught about PA and SB and may therefore be less likely to meet guideline-recommended levels of these two movement behaviours or promote them in practice. Few studies have examined the relationships between medical students’ PA intensity, SB, and burnout; such examination could help clarify educational needs for improving levels of movement behaviours and their promotion. Purpose: This study investigated (1) the relationships between light, moderate, vigorous, and total PA, SB, and burnout among medical students, and (2) moderate-to-vigorous PA as a moderator of the relationship between SB and burnout, to guide future curriculum renewal. Methods: Medical students (N = 129) at two Canadian institutions completed online validated questionnaires assessing light, moderate, vigorous, and total PA, SB, and burnout. Results: Regression analyses indicated that light PA (β = -.191, p = .039) and SB (β=-.230, p = .013) were negatively associated with burnout. Moderate-to-vigorous PA did not significantly moderate the relationship between SB and burnout. Conclusions: Engaging in lighter forms of PA and SB within guideline recommendations may help mitigate medical student burnout. Competencies to promote movement behaviours may dually target medical student burnout and curriculum gaps.